Dopaminergic modulation of emotional conflict in Parkinson's disease - Fleury, Vanessa; Cousin, Emilie; Czernecki, Virginie; Schmitt, Emmanuelle; Lhommée, Eugénie; Poncet, Antoine; Fraix, Valérie; Troprès, Irène; Pollak, Pierre; Krainik, Alexandre; Krack, Paul (Frontiers in Aging Neuroscience, 2014)
Neuropsychiatric fluctuations in Parkinson's disease (PD) are frequent and disabling. One way to investigate them is to assess the ability to inhibit distractive emotional information by a modified emotional Stroop (ES) task. We compared non-depressed, non-demented PD patients with healthy controls. During an acute levodopa challenge, patients performed a modified ES task during functional MRI and a neuropsychological assessment including Visual Analog Mood (VAMS) and Apathy scales. Ten patients and 12 controls completed the study. The VAMS scores were significantly improved by the acute intake of levodopa (p = 0.02), as was the apathy score (p = 0.03). Negative ES task (i.e. fearful facial expressions with the words “happy” or “fear” written across them), induced a lengthening of the mean reaction time during the incongruent trials compared with the congruent trials in controls (relative difference = 2.7%, p < 0.001) and in ON patients (relative difference = 5.9%, p < 0.001), but not in OFF patients (relative difference = 1.7%, p = 0.28). Controls and ON patients displayed greater activation than OFF patients within the right pregenual anterior cingulate cortex (pACC), an area specifically involved in emotional conflict resolution (p < 0.001 and p < 0.008 respectively, k > 5 uncorrected). No difference in the activation of the pACC was found between controls and ON patients, suggesting a normalization of the activation following levodopa administration. These results suggest that emotional conflict processes could be dopamine-dependent. Pregenual ACC hypoactivation could be directly due to the degeneration of dopaminergic mesocorticolimbic pathway. Our results propose that neuropsychiatric fluctuations in PD patients could be partially explained by pACC hypoactivation and that adjustments of dopaminergic medication might be helpful for their treatment.